A Framework for the Static and Interactive Visualization of Statecharts - Castelló, Rodolfo; Mili, Rym; Tollis, Ioannis (Journal of Graph Algorithms and Applications, 2002)
We present a framework for the automatic generation of layouts of statechart diagrams. Statecharts [] are widely used for the requirements specification of reactive systems. Our framework is based on several techniques that include hierarchical drawing, labeling, and floorplanning, designed to work in a cooperative environment. Therefore, the resulting drawings enjoy several important properties: they emphasize the natural hierarchical decomposition of states into substates; they have a low number of edge crossings; they have good aspect ratio; and require a small area. We also present techniques for interactive operations. We have implemented our framework and obtained drawings for several statechart examples. <!—->